Estimating food demand and the impact of market shocks on food expenditures: The case for the Philippines and missing price data - Valera, Harold Glenn; Mayorga, Joaquin; Pede, Valerien O.; Mishra, Ashok K. (Oxford University Press, 2022)
This study uses the Quadratic Almost Ideal Demand System to estimate food demand among Filipino households. Our study uses the recently released 2018 Family Income and Expenditure Survey and the Stone-Lewbel price index in the absence of price data on food groups. Results show that demand for rice with respect to prices and expenditures is relatively inelastic compared with that for other food groups. The income elasticity for rice is inelastic (0.26), slightly higher than the income elasticity for sugar. Demand for rice is generally less elastic for higher-income Filipinos and families residing in urban areas than for their counterparts. The findings reveal that, in the short term, a 15 per cent decrease in income or a 20 per cent increase in rice prices induces families to spend more of their income on rice at the expense of other cereals, meat, fish, and other food groups. Income and rice price shocks have differential impacts on low-income and high-income Filipino families. Policymakers may be able to moderate the food price impacts of market shocks through targeted interventions and programs that improve the accessibility to and availability of quality agri-fishery products.